2009
DOI: 10.1017/s1368980008004400
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel modelling of sociodemographic predictors of various levels of anaemia among women in Mali

Abstract: Objective: Anaemia currently affects 40-80 % of women in Africa. While risk factors for anaemia have been intensively studied, research has rarely compared risk factors between mild anaemia and moderate/severe anaemia. Also, the contribution of neighbourhood to the prevalence of anaemia has been rarely studied. The aim of the present study was to identify and compare individual and contextual factors associated with various levels of anaemia among women. Design: A multilevel analysis of data from the 2001 Mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
4
27
1
1
Order By: Relevance
“…Though studies have shown associations between low socioeconomic status and all anemia levels, our findings indicate that women with higher educational levels had higher odds of mild anemia [32, 34, 39]. We observed gender-specific variations in prevalence of anemia among different occupation groups.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Though studies have shown associations between low socioeconomic status and all anemia levels, our findings indicate that women with higher educational levels had higher odds of mild anemia [32, 34, 39]. We observed gender-specific variations in prevalence of anemia among different occupation groups.…”
Section: Discussioncontrasting
confidence: 48%
“…Many studies have shown inverse relationships between BMI and anemia [31, 32, 34, 42]. A multi-country, multi-level analysis of hemoglobin levels of African women showed stronger associations of anemia with socioeconomic and contextual factors than with BMI [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1985, global prevalence estimates for anemia have risen drastically (Stoltzfus, 2001). Estimates are particularly high in sub-Saharan Africa, where 40-80% of women are estimated to be anemic (Ngnie-Teta et al, 2007b, Ngnie-Teta, 2009). In the Democratic Republic of the Congo (DRC), 52.8% of non-pregnant women and 67.3% of pregnant women were estimated by the WHO to be anemic (less than 11 g/dl hemoglobin in the blood), making anemia a severe public health problem in the country (Who, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In women, anemia is associated with higher risk for maternal morbidity and mortality and lower productivity, and pregnant women are furthermore at higher risk for anemia. Maternal anemia may also lead to higher risks for premature births, perinatal and neonatal death, and low birth weight (Ngnie-Teta, 2009). Common symptoms include fatigue, weakness, fainting, chest pain, and even heart attacks in severe cases.…”
Section: Introductionmentioning
confidence: 99%